Determinants of Glycemic Control among Type 2 Diabetes Mellitus Patients in Primary Health Care - Detavia Rahma Purwono; Kezia Elian Devina; Dyah Ayu Wardani (Poltekkes Kemenkes Semarang, 2026)
Background: Glycemic control in patients with Type 2 Diabetes Mellitus (T2DM) is influenced by both modifiable and non-modifiable factors. Evaluating these factors is essential to achieve optimal glycemic control. Objective: This study aimed to analyze the determinants of glycemic control among patients with T2DM in the Karangmalang Primary Health Care area. Methods: This cross-sectional study involved 51 participants selected using purposive sampling. Data on participant characteristics and nutritional status were collected through questionnaires. Dietary adherence was assessed using the Perceived Dietary Adherence Questionnaire (PDAQ), while stress levels were measured using the Diabetes Distress Scale-17 (DDS-17). Glycemic control data were obtained from fasting blood glucose (FBG) measurements recorded over the previous three months in medical records. Data were analyzed using Pearson and Spearman correlation tests, followed by multiple linear regression analysis. Results: Glycemic control was significantly associated with age (p<0.001), education (p=0.007), income (p=0.016), duration of diabetes (p<0.001), family history of diabetes (p=0.016), medication adherence (p=0.016), nutritional status (p=0.004), dietary adherence (p=0.016), and stress level (p=0.016). Gender was not significantly associated with glycemic control (p=0.378). Multivariate analysis identified income, family history of diabetes, and medication adherence as the factors most strongly associated with glycemic control. Conclusion: Glycemic control among patients with T2DM was associated with age, education, income, duration of diabetes, family history of diabetes, medication adherence, nutritional status, dietary adherence, and stress level. Income, family history of diabetes, and medication adherence were the strongest determinants of glycemic control.